2020
DOI: 10.3390/su12125105
|View full text |Cite
|
Sign up to set email alerts
|

Wild Food Thistle Gathering and Pastoralism: An Inextricable Link in the Biocultural Landscape of Barbagia, Central Sardinia (Italy)

Abstract: In Sardinia, pastoralism has been at the heart of cultural identity for millennia. Such activity has shaped the landscape by sustainably managing its elements over the centuries. We conducted 30 semi-structured interviews regarding the uses of wild plants as well as their contribution to sheep breeding over the last few decades in two villages of Barbagia di Ollolai. We recorded the use of 73 taxa belonging to 35 families. Over one-third of the vernacular food taxa were mentioned as raw snacks. Specifically, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
4
22
0
Order By: Relevance
“…Some important wild food plants ( Figure 4 ) and dishes prepared by the visited communities were available for photographing ( Figure 5 ). Traditional culinary processing included cooking the plants as vegetables (43 mentions), followed by raw snacks (33), confirming what documented in other ethnobotanical studies too [ 73 , 74 , 75 ]. Raw snacks were eaten especially by transhumant herders, and it has been shown that herding develops specific linkages between humans and their surrounding ecosystem [ 76 , 77 , 78 , 79 ].…”
Section: Resultssupporting
confidence: 76%
“…Some important wild food plants ( Figure 4 ) and dishes prepared by the visited communities were available for photographing ( Figure 5 ). Traditional culinary processing included cooking the plants as vegetables (43 mentions), followed by raw snacks (33), confirming what documented in other ethnobotanical studies too [ 73 , 74 , 75 ]. Raw snacks were eaten especially by transhumant herders, and it has been shown that herding develops specific linkages between humans and their surrounding ecosystem [ 76 , 77 , 78 , 79 ].…”
Section: Resultssupporting
confidence: 76%
“…In addition, WFP are important as ancestors or relatives of cultivated, including major crop, plants [ 29 ], and as a reservoir of genes not present in domesticated taxa or races that could be useful for new crop developments [ 30 ]. Irrespective of their relevance, WFP have been the object of cultural erosion [ 31 ] and face conservation problems [ 32 ], this making their study and possible protection plans (comprising both plants and associated traditional knowledge) highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, snack foods provide small amounts of nutrients, mainly sugar and vitamins, but have had a relevant role as thirst quenchers and refreshments for shepherds and children while herding the sheep's and goats' flocks or looking after the pigs, as also have been documented in other Mediterranean regions (Łuczaj et al, 2013a;Mattalia et al, 2020b). The use of these species is associated with an extinct way of life, when shepherds and children spent long periods of time out in the countryside and ate wild plants to stave off the hunger or just to entertain themselves.…”
Section: Values Associated With the Food Contextmentioning
confidence: 96%
“…The use of these species is associated with an extinct way of life, when shepherds and children spent long periods of time out in the countryside and ate wild plants to stave off the hunger or just to entertain themselves. As several authors have argued, children (Łuczaj and Kujawska, 2012;Kalle and Sõukand, 2013) and shepherds (Mattalia et al, 2020b) have a wild food flora of their own, since the way they interact with nature shares some aspects with the hunter-gatherers, who wander around looking for something to eat for hours. As a female informant in her 70's told us: "when we were children we were always out in the country, with the cows, the sheep, the pigs.…”
Section: Values Associated With the Food Contextmentioning
confidence: 99%